Biotopic preferences of yellow wagtails in steppe conditions - E.A. Artemieva; D.A. Grudinin; V.A. Krivosheev (Известия высших учебных заведений. Поволжский регион: Естественные науки, 2023)
Background. Yellow wagtails are one of the key groups of ground–nesting Passeriformes birds of steppe communities. Data on the distribution and settlement density of yellow wagtails allow us to use the group as an indicator of the state of steppe communities. Material and methods. During the 2016-2022 field seasons, comprehensive studies of nesting biotopes of yellow wagtails were conducted in the steppe regions of Northern Eurasia: the Middle Volga Region, the Southern Urals, and the south of Western Siberia. The chemical composition of the soil and plant associations at sites in nesting biotopes of yellow wagtail colonies were analyzed. Results. Yellow wagtails prefer nesting biotopes in steppe conditions in the floodplains of salt lakes and steppe rivers characterized by the following chemical and mechanical features of the soil: pH from slightly acidic to neutral (Lim 4.7–7.8); organic matter content from moderate to high (Lim 3.0–14.3); phosphorus content from low to very high (Lim 20-460.0); potassium content from moderate to very high (Lim 65-1540); calcium content from moderate to very high (Lim 5.6–43.8); magnesium content from low to very high (Lim 1.5–17.1); the sulfur content is from low to high (Lim 2-15.0); copper content from moderate to high (Lim 2.6–8.8); zinc content from low to moderate (Lim 0.33–11.5); manganese content from moderate to high (Lim 5.2–86.5); mechanical composition of the soil – from sandy loam to medium clay (Lim 10.7–75). Conclusion. Yellow wagtails in steppe conditions prefer biotopes for nesting in the floodplains of salt lakes and steppe rivers, with pH-neutral soil, high in phosphorus and potassium, calcium, magnesium, copper and manganese and rather loose (from sandy loam and light loam to medium clay) , malleable for the device nesting fossa. Yellow wagtails are indicators of the conservation of steppe landscapes, salt lake floodplains, and soil features in halophytic steppe and meadow biotopes.